NMDAR encephalitis: passive transfer from man to mouse by a recombinant antibody. Issue 11 (3rd October 2017) - Malviya, Manish; Barman, Sumanta; Golombeck, Kristin S.; Planagumà, Jesús; Mannara, Francesco; Strutz‐Seebohm, Nathalie; Wrzos, Claudia; Demir, Fatih; Baksmeier, Christine; Steckel, Julia; Falk, Kim Kristin; Gross, Catharina C.; et al.
Abstract: Objective: Autoimmune encephalitis is most frequently associated with anti‐NMDAR autoantibodies. Their pathogenic relevance has been suggested by passive transfer of patients' cerebrospinal fluid (CSF) in mice in vivo. We aimed to analyze the intrathecal plasma cell repertoire, identify autoantibody‐producing clones, and characterize their antibody signatures in recombinant form. Methods: Patients with recent onset typical anti‐NMDAR encephalitis were subjected to flow cytometry analysis of the peripheral and intrathecal immune response before, during, and after immunotherapy. Recombinant human monoclonal antibodies (rhuMab) were cloned and expressed from matching immunoglobulin heavy‐ (IgH) and light‐chain (IgL) amplicons of clonally expanded intrathecal plasma cells (cePc) and tested for their pathogenic relevance. Results: Intrathecal accumulation of B and plasma cells corresponded to the clinical course. The presence of cePc with hypermutated antigen receptors indicated an antigen‐driven intrathecal immune response. Consistently, a single recombinant human GluN1‐specific monoclonal antibody, rebuilt from intrathecal cePc, was sufficient to reproduce NMDAR epitope specificity in vitro. After intraventricular infusion in mice, it accumulated in the hippocampus, decreased synaptic NMDAR density, and caused severe reversible memory impairment, a key pathogenic feature of the human disease, in vivo. Interpretation: A CNS‐specific humoral immune response is present in anti‐NMDAR encephalitis specifically targeting the GluN1 subunit of the NMDAR. Using reverse genetics, we recovered the typical intrathecal antibody signature in recombinant form, and proved its pathogenic relevance by passive transfer of disease symptoms from man to mouse, providing the critical link between intrathecal immune response and the pathogenesis of anti‐NMDAR encephalitis as a humorally mediated autoimmune disease.